[Proceedings of the] Regional conference for the world disarmament campaign (UN New YorkUS, 1986)
Includes presentations on topics related to the International Year of Peace 1986; the prevention of nuclear war and curbing the arms race; problems of verification of disarmaments; confidence and security building measures; and conventional weapons and measures of conventional disarmament. Contains reports of working groups on International Year of peace: education for peace; matters relating to nuclear disarmament; and matters relating to conventional disarmament. Includes list of participants.
Bibliography: p. 260-263